EVALUASI KINERJA VERTICAL DRAIN PADA PROYEK JALAN TOL DI SUMATERA DITINJAU DARI ASPEK KONSOLIDASI - Erika Oktavia; Andryan Suhendra (JMTS: Jurnal Mitra Teknik Sipil, 2021)
Over time, there has been more development, this has made less land for development. However, development still has to go on. One of the infrastructure that is currently needed is toll roads to increase the efficiency of movement from one place to another. One of the serious problems at this time is that many soils have small bearing capacity and large settlement, for example, such as soft soil. In order for this model soil to have a stable condition, the solution is loaded so that the pore water from the soil can be pressed out. However, it takes a long time to achieve the desired settlement, here the prefabricated vertical drain method is used to accelerate the settlement. Prefabricated vertical drain here makes the distance between the pore water that was previously thick as soft soil, to half the distance between prefabricated vertical drains. The analysis calculation in this thesis uses the one dimensional consolidation method, the finite element method, and the asaoka method as the calculation of the actual results from field data. The results of this study found that the difference in the degree of consolidation between the theoretical calculations and the Asaoka method was 3.4303%.